(untitled) (Research, Society and Development, 2025)
The objective was to evaluate the composition of the weed community in soybean crops after different autumn/winter crops under different doses and times of glyphosate application before soybean sowing. The experiment was conducted at Embrapa Agropecuária Oeste, in Dourados MS. The treatments evaluated were: T1: area of brachiaria desiccated 5 days before soybean sowing - DAS, with 2 L ha-1 of glyphosate; T2: brachiaria desiccated 5 DAS with 4 L ha-1; T3: brachiaria desiccated 30 DAS with 2 L ha-1; T4: brachiaria desiccated 30 DAS with 4 L ha-1; T5: desiccated consortium 5 DAS with 2 L ha-1; T6: desiccated consortium 5 DAS with 4 L ha-1; T7: desiccated consortium 30 DAS with 2 L ha-1; T8: desiccated consortium 30 DAS with 4 L ha-1; T9: desiccated cowpea 5 DAS with 2 L ha-1; T10: desiccated cowpea 5 DAS with 4 L ha-1; T11: desiccated cowpea 30 DAS with 2 L ha-1; T12: desiccated cowpea 30 DAS with 4 L ha-1; T13: desiccated corn 5 DAS with 2 L ha-1; T14: desiccated corn 5 DAS with 4 L ha-1; T15: desiccated corn 30 DAS with 2 L ha-1; T16: desiccated corn 30 DAS with 4 L ha-1. There were differences in weed diversity and infestation. Treatments with desiccation at 30 DAS showed greater dry mass among weed species. In short, in early desiccation there is a greater infestation of weeds, especially where there was cowpea and single corn as the predecessor crop at the lowest desiccation dose.